Analisis Faktor-faktor yang Mempengaruhi Keberhasilan Inisiasi Menyusu Dini - Warsini, Warsini; Wardani, Yunistya Kusuma (KOSALA : Jurnal Ilmu Kesehatan, 2019)
Background: IMD means the start of breastfeeding in the first hour after the baby is born. The implementation of IMD helps reduce poverty, reduce hunger and reduce child mortality. Although the benefits are very large, the coverage is still not optimal, which is less than the target of Healthy Indonesia 2010 at 80%. Objective: To find out what factors can influence the success of IMD in Kedunglumbu Village, Surakarta City. Subjects and Methods: Type of observational analytic study with crossectional design. The population of this study is mothers who have children aged 0-6 months in the Kedunglumbu area of Surakarta City in December 2018 to January 2019 with 32 being taken using saturated sampling techniques. Research Results: Most mothers were 29 years old, 5 mothers (15.6%), most of the mother's education levels were graduating from high school, as many as 27 mothers (44%), most of the mother's answer scores showed a good level of knowledge as many as 31 mothers ( 96.9%), most of the mothers did not work (IRT) as many as 16 mothers (50%), most of the mothers did not succeed in implementing IMD as many as 17 mothers (53.1%). The results of the analysis by Chi Square test showed that there was no relationship between the support of health workers and the success of IMD (p = 0.190), there was no relationship between family support and the success of IMD (p = 0.190), and there was no educational relationship with success in IMD (p = 0.340). Conclusion: There is no relationship between health worker support and the success of IMD (p = 0.190), there is no relationship between family support and the success of IMD (p = 0.190), and there is no educational relationship with the success of IMD (p = 0.340). Keywords: IMD, support, health personnel, family, education